Caracterização morfológica e funcional dos hemócitos da ostra Crassostrea gasar - Freire, Jesarela Merabe Silva (2022)
Hemocytes are the circulating cells of the hemolymph of oysters and are responsible for numerous physiological functions including immune defense. The oyster Crassostrea gasar is a native species that inhabits the mangrove and is of great commercial interest, being cultured throughout the Brazilian coast, mainly in the North and Northeast. Despite its commercial importance, little is known about immunological aspects and defense cells. This work aimed to morphologically characterize the hemocytes of the oyster C. gasar and to study one of the main cellular defense responses, the phagocytosis. The oysters were sampled in a commercial culture located in the estuary of the Mamanguape River, PB. The morphological characterization of the hemocytes was performed by light microscopy, where the hemocytes were adhered to slides and stained with Giemsa or neutral red, and flow cytometry was used to analyze the morphological parameters in cytograms. Phagocytosis was analyzed by flow cytometry using three fluorescent particles, one inert (latex) and two biological (zymosan A and Escherichia coli). The results showed the presence of six hemocytes populations in the C. gasar hemolymph, large and small granulocytes, large and small hyalinocytes and blast-like cells. Hyalinocytes were the most abundant cells and the most heterogeneous cell population, while small granulocytes were the less abundant population. A rare type of hemocyte was identified and classified as a vesicular cell. C. gasar oyster hemocytes were able to phagocytose three different types of particles: zymosan A, latex particles and Escherichia coli, indicating a broad defense capacity. The latex was the most engulfed particle by granulocytes that were the most phagocytic cells, while hyalinocytes phagocytized more E. coli bacteria. This study was the first characterization of C. gasar oyster hemocytes and will support future studies that aim to understand the participation of different hemocytes in defense responses against pathogens and/or environmental changes.